Connecting local active forces to macroscopic stress in elastic media. Issue 8 (28th February 2015) - Ronceray, Pierre; Lenz, Martin
<x xml:space="preserve">Abstract</x> Many living materials exert mechanical stresses on their environment that originate from internal forces generated by embedded active elements. We derive a general relation between microscopic forces and macroscopic stresses, which takes the form of a conservation of the force dipole across scales in linear elastic media.